Effects of a cognitive adjustment program for Thai parents - Sawasdipanich N. (2017)
Child physical abuse is recognized as a major public health problem that affects children and is likely to become increasingly common. The objective of this study was to examine the effects of a cognitive adjustment program on parental attitudes toward child rearing and the potential for this abuse. Child-care centers were randomly allocated to either the intervention or the control group. The sample included 116 Thai parents of children aged 1-6 years. The intervention group attended the cognitive adjustment program while the control group received the usual services. The results showed that, after program completion, the intervention group had statistically significantly better parental attitudes toward child rearing, but not a significantly lower potential for CPA than the control group. We concluded that the cognitive adjustment program was effective in altering parental attitudes toward child rearing. However, in order to enhance its efficacy, the program should be modified to be more intensive and it should be studied further for its effect on the potential for abuse. © 2010 Blackwell Publishing Asia Pty Ltd.